2011
DOI: 10.1371/journal.pone.0019055
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Gene Expression Changes Provoked by Bacterial and Fungal Infection in C. elegans

Abstract: While Caenorhabditis elegans specifically responds to infection by the up-regulation of certain genes, distinct pathogens trigger the expression of a common set of genes. We applied new methods to conduct a comprehensive and comparative study of the transcriptional response of C. elegans to bacterial and fungal infection. Using tiling arrays and/or RNA-sequencing, we have characterized the genome-wide transcriptional changes that underlie the host's response to infection by three bacterial (Serratia marcescens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
223
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(240 citation statements)
references
References 51 publications
14
223
0
Order By: Relevance
“…For this analysis and also all further assessments below, we considered a total of 111 differentially expressed gene sets from 35 transcriptome studies, which examined the C. elegans response to bacteria, fungi and one virus at various exposure time periods (electronic supplementary material, table S1). This confirms previous observations [50] and supports the role of NLP and CNC peptides as inducible anti-fungal effectors. One exception is infection with the Gram-positive bacterium Xenorhabdus nematophila, which induces the expression of several cnc and nlp genes (figure 2).…”
Section: (C) Caenacins and Related Peptidessupporting
confidence: 92%
See 2 more Smart Citations
“…For this analysis and also all further assessments below, we considered a total of 111 differentially expressed gene sets from 35 transcriptome studies, which examined the C. elegans response to bacteria, fungi and one virus at various exposure time periods (electronic supplementary material, table S1). This confirms previous observations [50] and supports the role of NLP and CNC peptides as inducible anti-fungal effectors. One exception is infection with the Gram-positive bacterium Xenorhabdus nematophila, which induces the expression of several cnc and nlp genes (figure 2).…”
Section: (C) Caenacins and Related Peptidessupporting
confidence: 92%
“…fungus versus bacterium) and site of infection (i.e. intestine versus epidermis) can influence effector gene expression in the worm [50].…”
Section: (C) Caenacins and Related Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 829 genes were upregulated and 461 genes were downregulated more than twofold in cdk-8 null mutants, representing 6.7% of all C. elegans genes (Table S1). To identify cdk-8-dependent gene programs, we compared our lists of cdk-8 regulated genes to other gene lists using EASE (Hosack et al 2003;Engelmann et al 2011). The top hit among genes upregulated in cdk-8 mutants was a set of genes upregulated in lin-35/Retinoblastoma (RB) synMuv gene mutants (Kirienko and Fay 2007), and lin-35-repressed genes also overlapped significantly with genes downregulated in cdk-8 mutants (Figure 2A).…”
mentioning
confidence: 99%
“…25,26 The signal transduction pathways responsible for induction of AMP expression in response to infection have been extensively characterized and reviewed recently. 27,28 In overview, at least two major pathways regulate epidermal AMP induction: a MAPK cascade required for induction of the neuropeptide-like (nlp) genes 23 ( Fig.…”
Section: Cutaneous Innate Immune Responses To Wounding and Infectionmentioning
confidence: 99%